Microbial nitrogen supply, nitrogen retention and rumen function in Menz sheep supplemented with dried leaves of multipurpose trees, their mixtures or wheat bran - Melaku, S.; Peters, Kurt J.; Tegegne, Azage (Elsevier, 2004)
The study was conducted at Debre Zeit Research Station of the International Livestock Research Institute in Ethiopia. Thirty-six male Menz sheep with a mean BW of 16.45+/-0.25kg were used in a completely randomized design. Nine treatment supplements consisting of wheat bran (positive control) or dried foliage of single multipurpose trees (MPTs), S. sesban 1198, S. sesban 15019, A. angustissima 15132, L. pallida 14203, or their mixtures were offered at 0.9% of BW on DM basis to sheep fed tef (Eragrostis tef) straw. Supplementation with the mixture of A. angustissima 15132 and both accessions of S. sesban promoted higher (PA. angustissima 15132. N retention was higher (PPPL. pallida 14203. Rams supplemented with the MPTs had higher (PA. angustissima 15132 and L. pallida 14203 were supplemented to animals in mixture with S. sesban 1198 or S. sesban 15019. Moreover, higher molar proportions of propionate in animals supplemented with the single MPTs and their mixtures compared to wheat bran suggested the potential benefits of the MPTs in improving energetic efficiency in the products of rumen fermentation. The results of the experiment showed A. angustissima 15132 to be an inferior supplement feed due to poor microbial N supply, N retention and rumen function in animals supplemented with it.